Results of paclitaxel (day 1 and 8) and carboplatin given on every three weeks in advanced (stage III-IV) non-small cell lung cancer - YUMUK, PERRAN FULDEN (BMC, 2005)
Background: Both paclitaxel ( P) and carboplatin ( C) have significant activity in non-small cell lung cancer (NSCLC). The weekly administration of P is active, dose intense, and has a favorable toxicity profile. We retrospectively reviewed the data of 51 consecutive patients receiving C and day 1 and 8 P chemotherapy (CT) regimen in advanced stage NSCLC to evaluate the efficacy and toxicity. Methods: Patients treated in our institutions having pathologically proven NSCLC, no CNS metastases, adequate organ function and performance status (PS) ECOG 0-2 were given P 112.5 mg/m(2) intravenously (IV) over 1 hour on day 1 and 8, followed by C AUC 5 IV over 1 hour, repeated in every three weeks. PC was given for maximum of 6 cycles. Results: Median age was 58 ( age range 39-77) and 41 patients (80%) were male. PS was 0/1/2 in 29/17/5 patients and stage was IIIA/IIIB/IV in 3/14/34 patients respectively. The median number of cycles administered was 3 ( 1 6). Seven patients (14%) did not complete the first 3 cycles either due to death, progression, grade 3 hypersensitivity reactions to P or lost to follow up. Best evaluable response was partial response (PR) in 45% and stable disease (SD) in 18%. Twelve patients (24%) received local RT. Thirteen patients (25%) received 2nd line CT at progression. At a median follow-up of 7 months (range, 1-20), 25 (49%) patients died and 35 patients (69%) progressed. Median overall survival ( OS) was 11 +/- 2 months (95% CI; 6 to 16), 1-year OS ratio was 44%. Median time to progression (TTP) was 6 +/- 1 months (95% CI; 4 to 8), 1-year progression free survival (PFS) ratio was 20%. We observed following grade 3 toxicities: asthenia (10%), neuropathy (4%), anorexia (4%), anemia (4%), hypersensitivity to P (2%), nausea/vomiting (2%), diarrhea ( 2%) and neutropenia (2%). Two patients (4%) died of febrile neutropenia. Doses of CT were reduced or delayed in 12 patients (24%). Conclusions: P on day 1 and 8 and C every three weeks is practical and fairly well tolerated outpatient regimen. This regimen seems to be comparably active to regimens given once in every three weeks.
Keywords: PHASE-II; RANDOMIZED-TRIAL; CHEMOTHERAPY; CISPLATIN; ETOPOSIDE; DURATION; TAXOL